1996
DOI: 10.1096/fasebj.10.9.8801179
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids and Hox genes

Abstract: The vertebrate embryonic body plan is constructed through the interaction of many developmentally regulated genes that supply cells with the essential positional and functional information they require to migrate to their appropriate destination and generate the proper structures. Some molecular cues involved in patterning the central nervous system, particularly in the hindbrain, are interpreted by the Hox homeobox genes. Retinoids can affect the expression of Hox genes in cells lines and embryonic tissues; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(107 citation statements)
references
References 51 publications
1
103
0
2
Order By: Relevance
“…It is well established that RA causes craniofacial malformations when administered during development (Durston et al, 1989;Gale et al, 1996;Marshall et al, 1996;Morris-Kay and Sokolova, 1996). These effects are produced by changes in the identity and migration patterns of the neural crest cells (Marshall et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that RA causes craniofacial malformations when administered during development (Durston et al, 1989;Gale et al, 1996;Marshall et al, 1996;Morris-Kay and Sokolova, 1996). These effects are produced by changes in the identity and migration patterns of the neural crest cells (Marshall et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The Role of RA Receptors and Prep1 in Actin-dependent HoxB Induction by RA Because RARs are important in HoxB expression in the neural region (Marshall et al, 1994(Marshall et al, , 1996Gould et al, 1998), we tested whether treatment with CytD affected the expression of any of these receptors. As shown in Table 3, CytD did not affect the expression levels of any of the RAR and retinoid X receptor (RXR) transcription factors, either in the absence or in the presence of RA.…”
Section: N-wasp Down-regulation Inhibits the Expression Of The Hoxb Cmentioning
confidence: 99%
“…Cell fate-determining clustered Hox genes are expressed colinearly in the same order as their location on the genome, generating anteriorto-posterior identities (Krumlauf, 1994). Several lines of evidence have demonstrated the importance of RA receptors (RARs) for patterning and basal expression of Hox genes in the vertebrate neural tube (Marshall et al, 1994(Marshall et al, , 1996Gould et al, 1998;Dupe et al, 1999). However, expression of anterior HoxB genes also depends on an auto-regulatory circuit involving the HoxB1 protein and the Prep1-Pbx1 complex (Marshall et al, 1996;Maconochie et al, 1997;Dupe et al, 1999;Jacobs et al, 1999;Ryoo et al, 1999;Ferretti et al, 2000Ferretti et al, , 2005Huang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that ATRA treatment rapidly led to the activation of p38 MAPK, followed by phosphorylation and proteasomal degradation of SRC-3 in primary cultured mouse embryo cortical neurons. Inhibition of p38 MAPK by SB203580 enhanced ATRA-induced transcriptional activity as indicated by increased specific binding of RARa to DR5-RARE and expression of HOXd3, one of the RA target genes responsible for CNS development (23,24). The rapid decrease of RARa in response to ATRA treatment occurred at 2 h after ATRA treatment and remained at a constant level through a period of 48 h treatment in primary cultured embryo cortical neurons.…”
Section: Introductionmentioning
confidence: 99%